Ways to Increase the Productivity and Quality of Mine Water Treatment - GUBINA, Natalia. A; YLESIN, Mikhail A.; KARMANOVSKAYA, Natalya V. (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018, 2018)
The article deals with the rational use of water resources, as well as protecting the environment from the harmful effects of human industrial activities. The aim of the study is to find ways to increase the productivity of existing treatment facilities and the quality of mine water treatment. The proposed solutions will lead to a reduction in discharges of untreated mine waters, a reduction in environmental payments and consumption of fresh water.